2016
DOI: 10.1021/acs.jpcc.6b01847
|View full text |Cite
|
Sign up to set email alerts
|

Redox Kinetics Study of Fuel Reduced Ceria for Chemical-Looping Water Splitting

Abstract: Chemical-looping water splitting is a novel and 8 promising technology for hydrogen production with CO 2 separation. that the reduction is the rate-limiting step, and it determines the total amount of hydrogen produced in the following oxidation 22 step. The redox kinetics is modeled using a two-step surface chemistry (an H 2 O adsorption/dissociation step and a charge-23 transfer step), coupled with the bulk-to-surface transport equilibrium. Kinetics and equilibrium parameters are extracted with 24 excellent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
92
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 64 publications
(175 reference statements)
9
92
0
Order By: Relevance
“…The temperature‐swing operation leads to lower efficiency and is harder to implement than isothermal processes . Isothermal redox systems have also been developed to overcome these disadvantages . Moreover, CO 2 splitting in an isothermal oxygen‐permeable membrane reactor that operates at temperature as high as 1500 °C was proposed in the 1980s and recently achieved on a ceria membrane .…”
Section: Introductionmentioning
confidence: 99%
“…The temperature‐swing operation leads to lower efficiency and is harder to implement than isothermal processes . Isothermal redox systems have also been developed to overcome these disadvantages . Moreover, CO 2 splitting in an isothermal oxygen‐permeable membrane reactor that operates at temperature as high as 1500 °C was proposed in the 1980s and recently achieved on a ceria membrane .…”
Section: Introductionmentioning
confidence: 99%
“…This concept has been applied to oxy-combustion ( Figure 35) [101,102,103,104]. The same reactor design ( Figure 35) has also been proposed for chemical looping water splitting with Pr-CeO 2 as the oxygen carrier [105]. Experimental results have shown that total hydrogen production can be 10-40 times the amount Figure 35: Schematic of rotary reactor for oxy-combustion [101] produced by thermochemical cycles [105].…”
Section: Chemical Looping Solar Reformermentioning
confidence: 99%
“…The same reactor design ( Figure 35) has also been proposed for chemical looping water splitting with Pr-CeO 2 as the oxygen carrier [105]. Experimental results have shown that total hydrogen production can be 10-40 times the amount Figure 35: Schematic of rotary reactor for oxy-combustion [101] produced by thermochemical cycles [105]. Moreover, the syngas produced has a CO/H 2 ratio close to 1:2 (ideal for other industrial processes), and there was minor carbon deposition [105].…”
Section: Chemical Looping Solar Reformermentioning
confidence: 99%
“…One approach is based on thermally reducing CeO 2 (solar driven) and then splitting CO 2 (and/or water) on the pre‐reduced oxide . Another viable way to access CO (or CO/H 2 mixtures) is the high‐temperature (co‐)electrolysis of CO 2 (and H 2 O) . Using in‐situ X‐ray photoelectron spectroscopy, the coupling between Ce 3+ /surface oxygen vacancy centers and carbonate intermediates has been shown .…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Another viable way to access CO (or CO/H 2 mixtures) is the high-temperature (co-)electrolysis of CO 2 (and H 2 O). [6][7][8][9][10][11] Using in-situ X-ray photoelectron spectroscopy, the coupling between Ce 3 + /surface oxygen vacancy centers and carbonate intermediates has been shown. [11] The dominant reactivity descriptor, rendering reduced ceria suitable for such applications, is the high redox reactivity and mobility of its oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%